Parasitoid Diversity of Whitefly and Aphid of Soybean - Rini Utami; Hari Purnomo; Purwatiningsih Purwatiningsih (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2014)
The research of parasitoid diversity of whitefly and Aphid on soybean were conducted at District of Lumajang from Juni to Agustus 2013. The objectives of this research were to study the biodiversity, abundance and parasitism of whitefly and Aphid parasitoid of soybean. Measurement of insect diversity was calculated using Shannon’s index. The result Showed, i.e. polynema sp (Hymenoptera: Mymaridae), Eretmocerus sp, Encarsia sp Aphelinus sp. (Hymenoptera: Aphelinidae) and Aphidius sp (Hymenoptera: Aphididae). Parasitoid were abundance in whitefly and aphid popular a soybean which is becomes a potential biocontrol pest management of whitefly and Aphid a soybean Keywords: Aphid , diversity, parasitoid, whitefly